An Analysis of the Readability Level of Arabic Textbooks Published by the Ministry of Religious Affairs Through the Cloze Test - Ambiya, Iza Zainal; Sauri, Sofyan (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2023)
The research investigates the readability level of Arabic textbooks published by the minister of religious affairs, especially the books for class IX of Arabic students measured through the cloze test. The researcher discussed this area because the readability aspect often needs more attention from textbook writers. The textbook writers sometimes use complex sentences without considering the age and cognitive level of the students, which impacts students' difficulty understanding the book's meaning. Furthermore, the teacher needs to evaluate the readability level of their occupation. The method of this research used qualitative research. The research sample is Class IX A of one of the MTs in Cirebon, consisting of 30 students. This research revealed six discourses in Arabic language textbooks of class IX students. Unfortunately, only three discourses are included in an instructional category appropriate to students' competency level, and two are included in the frustrated or difficult category. Meanwhile, one discourse consists of an independent or easy category. The overall average student score is 54%, which shows the books used for learning activities appropriate to the instructional level (Appropriate).